Building the barricade—DIY slit lamp breath shield - Zakariya Jarrar; Steven Harsum; Clara Hoi Ka Wu (BMJ Open Quality)
Ophthalmologists were concerned about the risk of SARS-COV-2 transmission via droplets given the close proximity to the patient during slit lamp examination. There is a need to design a simple, low-cost, waterproof breath shield to minimise risk of infection.Dimensions of the Haag-Streit slit lamp (model BM 900) were recorded to guide accurate design of the breath shield. A questionnaire was circulated among slit lamp users on their perceived risk and concern about SARS-CoV-2 transmission and their perception of how effective different designs of breath shields would be at protecting them from an infection. A number of breath shield prototypes were designed and trialled. Plan, Do, Study, Act (PDSA) cycles were used to improve the design. Materials used to create the breath shields included transparent A3 laminating pouches and laminator, two sheets of A4 paper, scissors, hole punch and a ruler. The breath shield was designed to fit over the objective lens on the slit lamp after temporarily removing the standard, manufacturer-provided breath shield, before replacing it. The breath shields were cleaned after every patient with alcohol wipes and removed for deep cleaning with hand soap and water after each session. We used a proof of concept experiment using fluorescein instilled spray to test the effectiveness of each breath shield at preventing droplet transmission to the slit lamp user.Following four PDSA cycles, a breath shield that is user-friendly, easy to clean was produced. The percentage of confidence that the final design would be effective at preventing droplet transmission increased from 5.6% to 80%.Implementation of a low cost, simple to make, transparent, waterproof breath shield together with other forms of person protective equipment (PPE) creates a safe working environment for clinicians and patients. This intervention can be readily replicated and modified for other slit lamp models.